Effect of PEAR1, PTGS1 gene polymorphisms on the recurrence of aspirin-treated patients with ischemic stroke in the Han population of China: A 4-year follow-up study - Zhang, Linlin; Meng, Zhongru; Wang, Hongxia; Miao, Yang (Medicine (Baltimore), 2024)
Platelet endothelial aggregation receptor 1 (PEAR1) and prostaglandin endoperoxide synthase 1 (PTGS1) polymorphisms can affect laboratory aspirin resistance. However, the impact of genetic polymorphisms on the recurrence of ischemic stroke (IS) patients treated with aspirin is not fully understood. This study aimed to examine the relationship between gene polymorphisms of PEAR1 and PTGS1 and IS recurrence in patients treated with aspirin. Peripheral blood samples were collected from 174 patients with nonrecurrent IS and 34 with recurrent IS after aspirin treatment. Follow-up was performed on all patients. PEAR1 rs12041331 and PTGS1 rs10306114 polymorphisms were determined using the PCR fluorescence probe method. And the correlations of them with the clinical characteristics were examined by multivariable logistic regression analysis. The distribution frequencies of PEAR1 rs12041331 and PTGS1 rs10306114 genotypes were in Hardy-Weinberg equilibrium, and there was no significant difference in the distribution of PEAR1 rs12041331 polymorphism. Compared to the nonrecurrent group, the AA genotype of the PTGS1 polymorphism was more frequent in the recurrent group (59.77% vs 35.29%, P = .003), and the A allele also showed a higher frequency than the G allele in the recurrent group (P = .001). Multivariable logistic regression analysis showed that smoking (OR = 5.228, 95% CI: 1.938-14.102, P = .001), coronary heart disease (OR = 4.754, 95% CI: 1.498-15.089, P = .008), and the polymorphism at PTGS1(A>G) AA/AG + GG (OR = 2.955, 95% CI: 1.320-6.616, P = .008) were independently associated with IS recurrence in Chinese patients. Our findings suggested that PTGS rs10306114 polymorphisms should receive more attention in the use of aspirin in patients with IS.